Psychometric Properties of the General Anxiety Disorder 7-Item (GAD-7) Scale in a Heterogeneous Psychiatric Sample - Johnson, Sverre Urnes; Ulvenes, Pål Gunnar; Øktedalen, Tuva; Hoffart, Asle (Frontiers in Psychology, 2019)
The GAD-7 is commonly used as a measure of general anxiety symptoms across various settings and populations. However, there has been disagreement regarding the factor structure of the GAD-7, and there is a need for larger studies investigating the psychometric properties of the measure. Patients undergoing treatment (N = 1201), both inpatient and outpatient patients, completed the GAD-7 at pre- and posttreatment. Measures of depression, well-being, and other anxiety measures were also completed, making it possible to investigate convergent and divergent validity. Internal consistency and convergent validity were excellent for the total sample, and there was acceptable variation related to treatment groups. We conducted an exploratory factor analysis (EFA) on a random sample (50%) of the patients at intake and then conducted a confirmatory factor analysis (CFA) to confirm the factor structure in the other part of the sample at intake. The EFA indicated a clear one-factor solution, but the one-factor solution with CFA provided a poor fit to the data. Correlating the residuals among items assessing somatic symptoms led to a good fit in a respecified CFA solution. The GAD-7 has excellent internal consistency, and the one-factor structure in a heterogeneous clinical population was supported.